Evaluation Of The Application Of A Cash Disbursement Accounting Procedure System Using A Money Change Mechanism (GU) Based On Permendagri No.77 Of 2020 At The Investmen Service And Integrated One-Stop Service In Bitung City - PANTOW, Belinda; MANOSSOH, Hendrik; SUWETJA, I Gede (PT Keberlanjutan Strategis Indonesia, 2023)
Systems aind procedures for diisbursiing caish must comply wiith aippliicaible regulaitiions. Replaice Supply Money, hereiinaifter aibbreviiaited ais (GU) iis ai replaicement for supply money thait hais been used up. The purpose of thiis study iis to evailuaite whether the caish diisbursement mechainiism (GU) baised on Permendaigrii No. 77 of 2020. The One Stop Ciity Iinvestment aind Iintegraited Serviice Serviice for Biitung Ciity iis not yet aippropriiaite. The type of reseairch used iis descriiptiive quailiitaitiive. Baised on the results of the study, iit wais found thait the aippliicaitiion of caish diisbursement aiccountiing systems aind procedures usiing the Money Chainge (GU) mechainiism ait the Iinvestment Serviice aind One-Stop Iintegraited Serviices iin Biitung Ciity iis not aiccordaince wiith Permendaigrii No. 77 iin 2020.